AFSFilter: artificial fish swarm filter-based algorithm for global optimization - Rocha, Ana Maria A. C. (2012)
A fish swarm intelligence algorithm based on the filter set concept to accept, at each iteration, a population of trial solutions whenever they improve constraint violation or objective function, relative to the current solutions, is proposed for constrained global continuous optimization problems. Preliminary numerical results are provided.